2021
DOI: 10.1158/1535-7163.mct-20-0717
|View full text |Cite
|
Sign up to set email alerts
|

Small Molecule Inhibitors of TEAD Auto-palmitoylation Selectively Inhibit Proliferation and Tumor Growth of NF2-deficient Mesothelioma

Abstract: Mutations in the neurofibromatosis type 2 (NF2) gene that limit or abrogate expression of functional Merlin are common in malignant mesothelioma. Merlin activates the Hippo pathway to suppress nuclear translocation of YAP and TAZ, the major effectors of the pathway that associate with the TEAD transcription factors in the nucleus and promote expression of genes involved in cell proliferation and survival. In this article, we describe the discovery of compounds that selectively inhibit YAP/TAZ-TEAD promoted gen… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
115
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 134 publications
(139 citation statements)
references
References 46 publications
8
115
0
Order By: Relevance
“…Quinacrine decreases YAP expression in NF2 mutant cells (Figure 4A), although the specific mechanism of action remains to be determined. Tang et al recently identified preclinical TEAD inhibitors for NF2-deficient mesothelioma, although toxicity studies have not been reported for these compounds (Tang et al, 2021). The preclinical success of TEAD inhibitors compliments our findings and highlights the potential benefits for repurposed drugs.…”
Section: Discussionsupporting
confidence: 83%
“…Quinacrine decreases YAP expression in NF2 mutant cells (Figure 4A), although the specific mechanism of action remains to be determined. Tang et al recently identified preclinical TEAD inhibitors for NF2-deficient mesothelioma, although toxicity studies have not been reported for these compounds (Tang et al, 2021). The preclinical success of TEAD inhibitors compliments our findings and highlights the potential benefits for repurposed drugs.…”
Section: Discussionsupporting
confidence: 83%
“…Therefore, it is a promising target for suppressing tumor progression and drug resistance [ 20 ]. Several YAP inhibitors have been discovered, including dasatinib, statin, pazopanib, verteporfin, and dobutamine [ 98 , 99 ]. Most drugs attenuate YAP-dependent transcription by inhibiting its nuclear translocation.…”
Section: Clinical Implication Of Yap Targeting and Verteporfin In Lung Cancermentioning
confidence: 99%
“…Although verteporfin is clinically used as a photosensitizer for photodynamic therapy, its off-target side effects and optimal dosage for anti-tumor effects should be considered. Recently developed drugs, including CA3, can potently and selectively interfere with the bond between YAP1 and TEAD [ 98 , 99 ]. These drugs may be valuable for targeting YAP in lung cancer.…”
Section: Clinical Implication Of Yap Targeting and Verteporfin In Lung Cancermentioning
confidence: 99%
“…This effect was initially demonstrated by two small-molecule inhibitors of TEAD palmitoylation, as well as by genetic studies. These observations were found both in vitro as well as in vivo [31][32][33]. Specifically, the inhibition of YAP1 activation and the subsequent reduction of already established tumors in vivo clearly demonstrate that YAP1 is a driver of tumor maintenance in malignant mesothelioma with the Hippo pathway or NF2 deletions.…”
Section: Targeting the Yap1/taz-tead Interactionmentioning
confidence: 65%
“…Specifically, the inhibition of YAP1 activation and the subsequent reduction of already established tumors in vivo clearly demonstrate that YAP1 is a driver of tumor maintenance in malignant mesothelioma with the Hippo pathway or NF2 deletions. Furthermore, NF2 deletions are also found in other tumor types such as renal cell carcinoma, cervical squamous cell carcinoma, schwannomas and meningiomas, which may hence respond equally well to the inhibition of YAP1 activation [33,34].…”
Section: Targeting the Yap1/taz-tead Interactionmentioning
confidence: 99%